Mukkudi - a polyherbal combination of drugs used in traditional postnatal care in north Kerala, India - P K Beena Rose; Anita K Patel; K V Asha (Journal of Traditional and Folk Practices (JTFP), 2021)
Postnatal care (sutika paricharana) is the management during the period from soon after the placental expulsion to one and half/second months. According to ayurveda paricharana should start with deepana pachana drugs. Mukkudi is one of the drug presentations used in the traditional sutika paricharana in north Kerala, as food and medicine in the week after delivery. It is mainly used as deepana, pachana, vathanulomana and stimulating lactation. It is a type of formulation coming under the upakalpana of kwathakalpana (pramatya kalpana) as well as in annavarga ( khala kalpana). The other formulations used in sutika paricharana are kurukkumarunnu (porridge) in the south and kashaya, lehya and kalka in north Kerala. Though the volume of knowledge in traditional postnatal care is very extensive.It differs according to caste, religion and geographical locations. Ayurvedic Samhitas, Nighandus, textbooks on ethnomedicine, and online publications were used to compile the relevant information in this regard. Data was also collected from 400 postnatal women from 4 zones by a questionnaire and directly from Ayurvedic experts, and traditional Vaidya families across Kerala. This paper highlights the prevalence of different formulations of mukkudi used in postnatal care from different places in north Kerala. Mukkudi kanji, mukkudi moru, mukkudi churnam, mukkudi marunnu, pettumukkudi and pettu podi are the major formulations. A total of 10.8% was used mukkudi preparations with a higher prevalence of 16.3% in zone C. As part of the study, collected different formulations of mukkudi, ingredients and indications of these formulations.